2006
DOI: 10.1592/phco.26.8.1157
|View full text |Cite
|
Sign up to set email alerts
|

Drug Copayment and Adherence in Chronic Heart Failure: Effect on Cost and Outcomes

Abstract: Among patients with CHF, higher drug copayments were associated with poorer adherence. The change was relatively small and did not affect predicted total health care costs, but it was sufficient to increase the predicted risk of hospitalization for CHF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 100 publications
(76 citation statements)
references
References 14 publications
3
72
1
Order By: Relevance
“…6,23 Smaller cohort studies in U.S. patients had similar findings regarding race, where minority or nonwhite race were significant predictors for nonadherence. 8,21 Other interesting findings from large cohort studies with follow-up ranging from 1 to 5 years in the United States, 6,23,32 Canada, 29 and European countries 22,27 identified those with more severe HF, 27 a greater a reduction in quality of life. [8][9][10][11][12][13][14] Furthermore, the Candesartan in Heart Failure Assessment of Reduction in Mortality and Morbidity (CHARM) study demonstrated that increased adherence to HF medications was associated with a 35% reduction in mortality (hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.57-0.75, P < 0.0001).…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 97%
See 3 more Smart Citations
“…6,23 Smaller cohort studies in U.S. patients had similar findings regarding race, where minority or nonwhite race were significant predictors for nonadherence. 8,21 Other interesting findings from large cohort studies with follow-up ranging from 1 to 5 years in the United States, 6,23,32 Canada, 29 and European countries 22,27 identified those with more severe HF, 27 a greater a reduction in quality of life. [8][9][10][11][12][13][14] Furthermore, the Candesartan in Heart Failure Assessment of Reduction in Mortality and Morbidity (CHARM) study demonstrated that increased adherence to HF medications was associated with a 35% reduction in mortality (hazard ratio [HR] = 0.65, 95% confidence interval [CI] = 0.57-0.75, P < 0.0001).…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 97%
“…6,8,10,12,[21][22][23][24][25][26][27][28][29][30][31][32] Table 1 may assist the health care provider in recognizing predictors that may impact adherence to HF medications. Table 2 depicts a summary of the studies identifying predictors of decreased 6,8,10,[21][22][23][24][25][26]28,29,32 and increased 8,12,22,[26][27][28]30,31 HF medication adherence. Large, observational cohort studies extracting adherence and demographic data from health insurance claims databases or HF registries with 2 to 4 years of follow-up data from the United States found some similar significant predictors for nonadherence, including male gender or nonwhite race.…”
Section: ■■ Results Predictors Of Medication Adherence In Heart Failurementioning
confidence: 99%
See 2 more Smart Citations
“…However, contradictory to the reduction of pharmacy visitation days, the total pharmacy costs increased, which shows similar results to the above. That is, medical expenditures for medical services increased, which did not impact the total amount of medical expenditures [18,19].…”
Section: Discussionmentioning
confidence: 98%